Effect of different treatments on the dissipation and persistence of iodosulfuron-methyl applied in soils with wheat crop under greenhouse conditions - María José Carpio; Sabrina Bárcena; María Jesús Sánchez-Martín; Jesús M. Marín-Benito; M. Sonia Rodríguez-Cruz (Ecotoxicology and Environmental Safety)
The herbicides used on primary crops in rotational agriculture may be phytotoxic for subsequent ones, and their behaviour needs to be studied under different soil, climate, and agronomic conditions. This research therefore sought to study the effect of different agronomic treatments (i.e., application of organic amendment, and different herbicide doses and irrigation regimes) on the dissipation and persistence of the herbicide iodosulfuron-methyl-sodium applied to post-emergence wheat in two agricultural soils under controlled greenhouse conditions. Two soils with different pH (4.4 for SA and 6.0 for SB) were sampled from the Muñovela farm (NW Spain) and amended with green compost (GC) at 2.5 % (w/w) (SA+GC and SB+GC). Wheat was sown in pots with unamended and amended soils. Each soil was treated with two herbicide doses (D1, agronomic dose, and D2, double dose) and under two irrigation regimes (AR, average rainfall, and MR, minimum rainfall). To study the persistence of the herbicide, the dissipation curve was obtained by plotting the percentage of herbicide remaining in samples of the surface soil collected from all the pots at different times (0–56 days), determined by HPLC-MS versus time, and the data were fitted to different kinetic models to calculate the half-life (DT50). The amounts of the herbicide remaining in the soil profiles were quantified for the different treatments at 90 days. Soils with a higher organic carbon (OC) content and pH (SA+GC, SB, and SB+GC) recorded significant lower DT50 values than SA (p < 0.05), due to higher herbicide adsorption by these soils. The soils under the AR regime had a faster dissipation rate compared to the soils under MR regime, which favoured the persistence of the herbicide. The persistence study revealed a higher concentration of herbicide remaining in the surface layer of the soil, especially in SA+GC and SB+GC. Overall, the herbicide persisted for a longer time in the GC-amended soils, treated with D2 dose and under MR regime.